Intergenerational Influence and Quality of Life: A Study Within Families with a Child with a Disability - Femke Migerode; Ann Buysse; Lesley Verhofstadt; Bea Maes; Jan De Mol (Psychologica Belgica, 2013)
The aim of the present study was to investigate (a) how intergenerational influence takes form within families with a child with a disability, and (b) the extent to which positive and negative influence – as perceived by family members – within and across generations, is predictive of family members' subjective quality of life. The study involved 60 two-parent two-child families where one of the children had a disability. Within a round-robin design, family members completed self-report measures of felt influence within their family and subjective quality of life. The main findings suggest that interpersonal influence as perceived by parents and children (a) varies as a function of valence (positive vs. negative) and target (from whom the influence is felt); and (b) is related to subjective quality of life. However, there seem to be differential effects of the distinct dimensions of influence (positive vs. negative; intergenerational vs. intragenerational) depending on whose quality of life is examined.